Karakteristik Kasus Kekerasan Seksual di Rumah Sakit Tipe A di Jawa Barat dan Sumatera Barat - Windasari, Noverika (Jurnal Kesehatan Andalas, 2020)
Introduction: Sexual assault in women and children are very prominent among other abuse. Knowledge related to the characteristics of sexual assault is vital for optimal handling of sexual assault cases. Aims: This research aimed to evaluate the characteristics of sexual assault cases in referral hospital (type A hospital) in West Java and West Sumatera provinces. Method: This research is a retrospective descriptive research. The samples were patients suspected of being victims of sexual assault, examined from 1 January 2014 to 31 December 2018. Results: The alleged sexual assault victims are dominated by women, unmarried, with the most age groups of 10-19 years. Most victims come to the hospital within a week after the case. The primary type of sexual assault experienced by the victims is vaginal penetration. Most perpetrators were someone who was well known by the victims. The perpetrators prefer to act at noon in a private place. Medical records revealed that in most cases only signs of violence on the anogenital region, and no trace on other body parts. Conclusion: The characteristic of sexual assault from both provinces are almost similar. The difference that stands out lies in the level of education of victims. Knowledge about the aspects of sexual assault cases is essential for health service to provide optimal health service to sexual violence victims as well as the prevention efforts.